Support to Jobs for Youth in Niger : A Retrospective Evaluation of Jobs Projects 2007-2018 - Gado, Boureima; von der Goltz, Jan; Saidi, Mira; Soumaila, Abdoulaye Sambo (World Bank, Washington, DC, 2019)
Supporting jobs for youth in Niger means addressing difficult questions of the right level of ambition, of reaching the necessary scale, and of trade-offs with funding for poverty reduction. Jobs policy for youth in Niger faces a difficult balancing act. It must be grounded in the reality that given the very modest starting point, economic opportunities for most Nigeriens are likely to remain limited in the medium term. At the same time, jobs policy needs to contend with the fact that young Nigeriens aspire for a different economic life than that lived by their elders. The challenge is thus to determine what kind of support is realistically feasible and can provide a good-enough perspective for young Nigeriens. Secondly, policy must ask whether the actions envisaged can make a real difference at scale, given the very big needs for better jobs. Finally, in an environment where poverty remains pervasive, it is important to acknowledge that providing jobs support specifically for youth may mean forgoing other investments that may be more efficient in reducing poverty. To make informed choices on these questions, policy makers may need to understand clearly the effectiveness of different jobs support modalities, their appropriateness in addressing Niger`s challenges, and their cost efficiency. This study seeks to provide such an assessment. The purpose of this study is to review the effectiveness of projects that supported jobs for youth in Niger over the years 2007-2018.